2006
DOI: 10.1073/pnas.0601515103
|View full text |Cite
|
Sign up to set email alerts
|

Monoamine oxidase A and repressor R1 are involved in apoptotic signaling pathway

Abstract: Monoamine oxidase A (MAO A) degrades serotonin, norepinephrine, and dopamine and produces reactive oxygen that may cause neuronal cell death. We have previously reported that a novel transcription factor R1 (RAM2͞CDCA7L͞JPO2) inhibits the MAO A promoter and enzymatic activities. This study reports the roles of MAO A and R1 in apoptosis and proliferation. We have found that in serum starvation-induced apoptosis, p38 kinase, MAO A, and caspase-3 were increased, whereas Bcl-2 and R1 were reduced. Using a p38 kina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
145
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 146 publications
(148 citation statements)
references
References 27 publications
(21 reference statements)
3
145
0
Order By: Relevance
“…These studies and our current study demonstrated that MAO A may be an important enzyme that regulates the brain structure at a critical neuronal developmental stage, which is important for the development of brain structures and behaviors in adults. In addition, we have found a new function of MAO A and its novel repressor R1 (RAM2/ CDCA7L/JPO 2 ) in apoptosis and c-Myc-induced cell cycle signaling pathway (38). The various MAO KO animal models generated, including MAO A KO, MAO B KO, MAO AB double KO, and forebrain-specific human MAO A transgenic MAO A KO generated here, would be valuable for further studying the role of MAO A and neurotransmitters, 5-HT, NE, and DA, in neuronal development, brain structure, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…These studies and our current study demonstrated that MAO A may be an important enzyme that regulates the brain structure at a critical neuronal developmental stage, which is important for the development of brain structures and behaviors in adults. In addition, we have found a new function of MAO A and its novel repressor R1 (RAM2/ CDCA7L/JPO 2 ) in apoptosis and c-Myc-induced cell cycle signaling pathway (38). The various MAO KO animal models generated, including MAO A KO, MAO B KO, MAO AB double KO, and forebrain-specific human MAO A transgenic MAO A KO generated here, would be valuable for further studying the role of MAO A and neurotransmitters, 5-HT, NE, and DA, in neuronal development, brain structure, and behavior.…”
Section: Discussionmentioning
confidence: 99%
“…In brain tissue, MAO-A level is highly correlated with MAO-A activity and MAO-A V T is primarily an index of MAO-A level (Saura et al, 1992). Elevated MAO-A activity is related to several important downstream effects, as MAO-A participates in the metabolism of serotonin, dopamine, and norepinephrine, produces the pro-oxidant hydrogen peroxide and influences the predisposition toward apoptosis (Fitzgerald et al, 2007;Ou et al, 2006b;Youdim et al, 2006). The specific regions assayed in this study, which have a reasonably high MAO-A density, also participate in neural systems dysregulated during MDE and elevations of MAO-A V T in these regions could potentially account for the individual symptoms of MDE.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation with secondary antibody, stained slides were mounted with Vectashield in the presence of 4,6-diamino-2-phenylindole (DAPI nuclear stain, Vector Lab, Inc.) (17).…”
Section: Methodsmentioning
confidence: 99%